Belgrade’s urban transformation during the 19th century: a space syntax approach - Fouillade Orsini, Hadrien (Geographica Pannonica, 2018)
This paper focuses on the change in terms of spatial structure of the city centre of Belgrade occurred during the 19th century with the urban renewal and sprawl. Space Syntax methodology was used in order to analyse and quantify the spatial configuration properties of the old town inherited from the Medieval and Ottoman period, but also to understand the changes produced by the remodelling of the borough during the Principality of Serbia according to the academic architectural style. A scan from the Radoje Dedinac plan of Belgrade from 1815-1830 conserved at the City Museum of Belgrade has been used in order to capture the old town morphology. Despite an abundant literature describing the incredible metamorphosis of the oriental part of the old town, the sources that have scientifically evaluated the urban transformation produced are very few. The Space Syntax methodology helps filling this gap. Axial maps of Belgrade between 1815-1830 and of nowadays have been generated and analysed in order to capture spatial intelligibility and synergy of the city before and after the urban transformation. Finally angular segment analysis has been used to understand the spatial morphology of both the organic urban form and the modern grid system.